1998
DOI: 10.1021/jf980286f
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Imidacloprid from a Lignin Matrix: Water Release Kinetics and Soil Mobility Study

Abstract: Formulations of the insecticide imidacloprid were made using a commercially available pine kraft lignin. The release kinetics of imidacloprid from granules with variation in the loadings of the insecticide and granule sizes were evaluated in water under dynamic flow conditions. The release data were fitted to the generalized model M t /M z = kt n + c, where M t /M z is the percentage of insecticide released at time t, k and c are constants, and n is another constant that indicates the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 13 publications
5
51
0
1
Order By: Relevance
“…Technical information regarding the controlled release formulation of Admire CR was unknown; however, it was reported as an example of the controlled release formulation of imidacloprid that the inactive ingredient in the controlled release formulation was made by adsorptive materials or sorbents, 3,18) which allow active ingredients to be slowly released to water. T 50 (time taken for 50% of the pesticide to be released) of imidacloprid in Admire was less than 1 day and Admire CR was about 20 days, respectively at 25 of imidacloprid in several controlled release formulations was 0.6-6.5 days for lignin-based formulations, 19) 14.6-18.7 hr for alginate-bentonite formulations, 11) 0.9-12 days for lignin formulations, 17) and 7.6-6290 hr for alginate-bentonite-activated carbon formulations.…”
Section: Pesticide Behavior In Paddy Water and Paddy Surface Soilmentioning
confidence: 94%
See 1 more Smart Citation
“…Technical information regarding the controlled release formulation of Admire CR was unknown; however, it was reported as an example of the controlled release formulation of imidacloprid that the inactive ingredient in the controlled release formulation was made by adsorptive materials or sorbents, 3,18) which allow active ingredients to be slowly released to water. T 50 (time taken for 50% of the pesticide to be released) of imidacloprid in Admire was less than 1 day and Admire CR was about 20 days, respectively at 25 of imidacloprid in several controlled release formulations was 0.6-6.5 days for lignin-based formulations, 19) 14.6-18.7 hr for alginate-bentonite formulations, 11) 0.9-12 days for lignin formulations, 17) and 7.6-6290 hr for alginate-bentonite-activated carbon formulations.…”
Section: Pesticide Behavior In Paddy Water and Paddy Surface Soilmentioning
confidence: 94%
“…[17][18][19] The release rate of active ingredient from granules depended on the characteristics of sorbents, 8,18) sizes of the granules, 16,17,19) loading mass of the pesticide, and physicochemical properties, such as the aqueous solubility and lipophilicity of pesticides. 8,16,18,19,24) The mechanism of dissolution and sorption of imidacloprid for BT and AS treatments in rice paddy fields is elucidated in the Fig.…”
Section: Pesticide Behavior In Paddy Water and Paddy Surface Soilmentioning
confidence: 99%
“…30) Other studies also found the downward movement of imidacloprid in the soil column. 27,33,34) In a paddy lysimeter study, Oi et al found that imidacloprid was not detected in the leachate (<0.2 μg/L), 35) and the concentration of imidacloprid in the 5-30 cm soil layer a er harvesting (about 4 months a er transplanting) was less than 5 μg/kg for both volcanic ash soil and alluvial soil. e residue of imidacloprid in the lysimeter soil pro le before harvesting in the study of Oi et al is unknown and a direct comparison cannot be made with the residue of imidacloprid in the MPL soil prole at 21 DAT in our study; 35) however, the average concentrations of imidacloprid in 5-15 cm were 13.6 and 8.8 μg/kg, respectively, with AS and BT treatment, which is comparable to the above nding of Oi et al (1994) considering the sampling depth and monitored time.…”
Section: Imidacloprid Fate and Transport In Paddy Soilmentioning
confidence: 99%
“…e reported T 50 of imidacloprid in several controlled release formulations ranged from a few hours to several months depending on the granular size and formulation type. [25][26][27][28] Figure 4a shows the concentrations of imidacloprid in di erent soil layers: 0-2.5 cm, 2.5-5 cm, 5-7.5 cm, 7.5-10 cm, 10-12.5 cm, and 12.5-15 cm in S1 (BT treatment) and S2 (AS treatment) at 21 DAT, respectively. From the top to bottom layer, the concentrations fell exponentially in both S1 and S2.…”
Section: Dissipation Kinetics Of Imidacloprid In Paddy Watermentioning
confidence: 99%
“…Embora existam esforços consideráveis na investigação de vários aspectos de formulações para liberação in vitro de pesticidas, aplicações comerciais permanecem escassas, em função do alto custo de produção em comparação ao uso de granulados no solo [5] . Entre os materiais que podem ser empregados na microencapsulação, encontram-se os polímeros obtidos de fontes naturais como os polihidroxialcanoatos e os poliésteres sintéticos como as policaprolactonas [12,13] . Os polihidroxialcanoatos são poliésteres termoplásticos sintetizados por várias bactérias a partir de fontes renováveis [14] .…”
Section: Introductionunclassified